Dampak Digitalisasi Pembayaran QRIS terhadap Budaya Perencanaan Keuangan Gen-Z - Resti Agustini; Nurulita Syafrida; Rudi Sanjaya (International Forum of Researchers and Lecturers, 2024)
Digitalization in the payment system has brought significant changes in people's behavior, including among generation Z (Gen-Z). One of the most prominent innovations is the Quick Response Code Indonesian Standard (QRIS), which offers convenience, speed, and accessibility in transactions. This study aims to analyze the impact of implementing QRIS payments on the financial planning culture of Gen-Z, known as the digital native generation. This study uses a quantitative approach with a survey method on a number of respondents from Gen-Z. The results of the study show that the use of QRIS has positive and negative impacts on their financial planning habits. On the one hand, QRIS makes it easier to manage daily financial transactions, such as automatic recording and easy cashless payments. On the other hand, this convenience also has the potential to increase consumptive behavior due to too fast access and minimal direct control over spending. This study highlights the importance of financial education to increase Gen-Z's awareness in using technology wisely to support better financial planning.